Impact Evaluation of Stop Violence Against Women Grants in Dane County, Wisconsin, Hillsborough County, New Hampshire, Jackson County, Missouri, and Stark County, Ohio, 1996-2000 - Uekert, Brenda K. ([Verlag nicht ermittelbar], 2001)
In 1996 the Institute for Law and Justice (ILJ) began an evaluation of the law enforcement and prosecution components of the "STOP Violence Against Women" grant program authorized by the Violence Against Women Act of 1994. This data collection constitutes one component of the evaluation. The researchers chose to evaluate two specialized units and two multi-agency team projects in order to study the local impact of STOP on victim safety and offender accountability. The two specialized units reflected typical STOP funding, with money being used for the addition of one or two dedicated professionals in each community. The Dane County, Wisconsin, Sheriff's Office used STOP funds to support the salaries of two domestic violence detectives. This project was evaluated through surveys of domestic violence victims served by the Dane County Sheriff's Office (Part 1). In Stark County, Ohio, the Office of the Prosecutor used STOP funds to support the salary of a designated felony domestic violence prosecutor. The Stark County project was evaluated by tracking domestic violence cases filed with the prosecutor's office. The case tracking system included only cases involving intimate partner violence, with a male offender and female victim. All domestic violence felons from 1996 were tracked from arrest to disposition and sentence (Part 2). This pre-grant group of felons was compared with a sample of cases from 1999 (Part 3). In Hillsborough County, New Hampshire, a comprehensive evaluation strategy was used to assess the impact of the use of STOP funds on domestic violence cases. First, a sample of 1996 pre-grant and 1999 post-grant domestic violence cases was tracked from arrest to disposition for both regular domestic violence cases (Part 4) and also for dual arrest cases (Part 5). Second, a content analysis of police incident reports from pre- and post-grant periods was carried out to gauge any changes in report writing (Part 6). Finally, interviews were conducted with victims to document their experiences with the criminal justice system, and to better understand the factors that contribute to victim safety and well-being (Part 7). In Jackson County, Missouri, evaluation methods included reviews of prosecutor case files and tracking all sex crimes referred to the Jackson County Prosecutor's Office over both pre-grant and post-grant periods (Part 8). The evaluation also included personal interviews with female victims (Part 9). Variables in Part 1 (Dane County Victim Survey Data) describe the relationship of the victim and offender, injuries sustained, who called the police and when, how the police responded to the victim and the situation, how the detective contacted the victim, and services provided by the detective. Part 2 (1996 Stark County Case Tracking Data), Part 3 (1999 Stark County Case Tracking Data), Part 4 (Hillsborough County Regular Case Tracking Data), Part 5 (Hillsborough County Dual Arrest Case Tracking Data), and Part 8 (Jackson County Case Tracking Data) include variables on substance abuse by victim and offender, use of weapons, law enforcement response, primary arrest offense, whether children were present, injuries sustained, indictment charge, pre-sentence investigation, victim impact statement, arrest and trial dates, disposition, sentence, and court costs. Demographic variables include the age, sex, and ethnicity of the victim and the offender. Variables in Part 6 (Hillsborough County Police Report Data) provide information on whether there was an existing protective order, whether the victim was interviewed separately, severity of injuries, seizure of weapons, witnesses present, involvement of children, and demeanor of suspect and victim. In Part 7 (Hillsborough County Victim Interview Data) variables focus on whether victims had prior experience with the court, type of physical abuse experienced, injuries from abuse, support from relatives, friends, neighbors, doctor, religious community, or police, assistance from police, satisfaction with police response, expectations about case outcome, why the victim dropped the charges, contact with the prosecutor, criminal justice advocate, and judge, and the outcome of the case. Demographic variables include age, race, number of children, and occupation. Variables in Part 9 (Jackson County Victim Interview Data) relate to when victims were sexually assaulted, if they knew the perpetrator, who was contacted to help, victims' opinions about police and detectives who responded to the case, contact with the prosecutor and victim's advocate, and aspects of the medical examination. Demographic variables include age, race, and marital status.